Semantic of the bilobulated image of the head in the ancient man of the central andean coast of Chancay—Ancón (Peru). A relationship with the Lunar goddess— goddess of the Sea? - Yépez Vásquez, Zoila Rosaura (2021)
The Chancay-Ancón cultures (1200–1400 years AD), carried out the cultural practice of cephalic modeling, both groups show the oblique fronto occipital type of modeling and others in the erect type, with a distinctive cephalic trait, “a bilobed symbolic head shape”, which is represented in anthropomorphic ceramic art from the Middle Horizon (800-1100 AD) to the Late Horizon and the Inca conquest (1200-1532 AD). In the same way, this "form of cephalic modeling" is represented by the goddess of the Sea (or Earth goddess, or Moon goddess). Therefore, this dimension of Andean thought, would be alluding to what the head with a bilobed image among the ancient coastal people, would be associated with the lunar cults, or there could be a relationship of identity or fertility with the body image of the Lunar goddess, goddess Earth or goddess of the Sea. In this regard, What reciprocity relationship could exist between the “bilobed image of the head” of the ancient Chancay-Ancón inhabitant, with the “bilobed image of the head of the Sea goddess–Lunar goddess or Earth goddess?